IMPLEMENTASI ALGORITMA APRIORI UNTUK MEBANTU PROSES PERSEDIAAN BARANG - MATOVANI, DIO; HADIONO, KRISTOPHORUS (Information Technology and Telematics, 2018)
Abstract - Currently technological advances make it easier for supermarkets that use information technology to conduct transactions, all products sold automatically enter the database. Even though we have used computers for transaction and data storage activities, the management of the supply of goods in our shop is still not good. The object of this research is TokoKita which is located in Pemalang Regency, Randudongkal Subdistrict, Randudongkal Village. The TokoKita transaction data used was November 2016 to October 2017 the data was used to explore information on the relevance of an item. The research method used in this study is CRISP-DM which consists of business understanding, data understanding, data preparation, modeling, evaluation, and deployment. There are several methods or algorithms contained in data mining science can be used to help get the information needed in planning the purchase of goods inventory, namely the rules of association (association rule) using a priori algorithm. This study produced several rules, one of them is 899190610101DJARUM 12 → 899898910012GG FILTER 12 which means that every purchase of 899190610101DJARUM 12 → 899898910012GG FILTER 12 has support as much as 0.02485575 with each purchase of items 899190610101DJARUM 12 has a level of confidence = 0.3063852 to buy 899898910012GG FILTER 12.